Trends in adolescent unions and childbearing in four Central American countries - Remez, Lisa; Singh, Susheela; Prada, Elena (Población y Salud en Mesoamérica, 2009)
Context: Four low-income Central American nations—El Salvador, Guatemala, Honduras and Nicaragua—have the highest rates of adolescent fertility in Latin America. More information on time trends in adolescent marital and reproductive behaviors is needed to assess the need for improved information and services to delay marriage and childbearing. Methodology: Data from these countries’ recent Demographic and Health Surveys and Reproductive Health Surveys are used to examine trends in adolescent unions and childbearing by comparing two cohorts roughly a generation apart, 40–44-year-olds and 20–24-year-olds. We tested for significant differences over time, both for women overall and within subgroups, using Pearson Χ2 statistics that take the stratified, cluster sample design into account. Findings: As of 2001–2005/6, adolescent unions, which are far more likely to be consensual than legal, were still widespread in the subregion, as 45–60% of 20–24-year-old women in these four countries had entered into a union before their 20th birthday. Nonetheless, such early unions have fallen significantly over time in all four countries, declining by relatively less in Honduras (by six percentage points) than in the other three countries (by 10–15 percentage points). In contrast, no comparable uniform trend emerged in the timing of first births: The proportions giving birth before age 20 fell significantly only in Nicaragua (by eight points); declines were smaller and nonsignificant in the other three countries (2–5 points). At the subgroup level, just one change was significant within area of residence—the 12-point decline in the proportion with any adolescent birth in urban areas in Nicaragua. Although the change was not significant at the population level, adolescent births increased significantly among less-educated women and the poorest women in El Salvador and Honduras, as traditional behaviors likely became more concentrated in those subgroups of women that shrank over time. Conclusions: Possible reasons for why first births did not decline in tandem with first unions in El Salvador, Guatemala and Honduras include greater pressure and desire to conceive sooner after entering a union and a possible increase in premarital conceptions and childbearing. Since evidence suggests that women are having now fewer second- and third-order births during adolescence but not necessarily postponing a first birth until after age 20, more innovative strategies are needed to help them adopt contraceptive use before rather than after a first birth.